Keratoconus in Eastern Mediterranean Region: Prevalence and risk factors - Zoelfigar D. Mohamed (African Vision and Eye Health, 2025)
Background: Keratoconus (KC) is common in areas with disease-related risk factors. It is characterised by progressive, non-inflammatory thinning of the cornea with unknown causes and is likely multifactorial.